PERTUMBUHAN DAN HASIL SELADA (Lactuca sativa L.) PADA PERBEDAAN JENIS PUPUK ORGANIK CAIR - Atikah . .; Arzita . . (Bioplantae, 2014)
The experiment aimed to determine the interaction of liquid organic fertilizer on growth and yield of two varieties of lettuce. This experiment used a randomized complete block design with factorial pattern. Lettuce variety is the first factor: Variety Lettuce (v1) and  Grand Rapid (v2) and second factor is organic fertilizers: control, without liquid organic fertilizers application, Golden Harvest, Grow Quick and Alam Natural. The results showed there was significant interaction between the type of liquid organic fertilizer and varieties. The highest lettuce fresh weight was achieved at variety Lettuce with liquid organic fertilizer Golden Harvest.Keywords: ertilizer, lettuce, growth, liquid, variety